Effects of shock waves on the rat foetus - Yalçin, O; Tahmaz, L; Yumbul, Z; Bilgiç, J; Saglam, R (Scandinavian University Press, 1998)
Controversy exists concerning whether shock wave lithotripsy (SWL) is contraindicated during pregnancy (4, 5). The effects of shock waves on a variety of cells are well documented in both clinical and experimental studies, but their effect on the foetus remains unclear. In this study, we investigated the effects of SWL on the rat foetus. On the 8th, 11th, 14th and 17th days of pregnancy, 100, 250 or 500 shock waves were administered with a Multimed 2001 ELMED Systems Lithotriptor. In ongoing pregnancy, the effects of SWL on the foetus ranged from early mild effects to later moderate effects and fatal effects. There were no viable foetuses in the latest period of pregnancy in rats receiving 500 shocks waves. Histological changes were observed in the brain, lungs and subcutaneous tissue. Fusion and necrosis were found in many dead foetuses. Our study demonstrates that SWL causes foetal damage and death in the late period of pregnancy in rats.
Keywords: pregnancy; rat; SWL